Along but beyond mean-variance: Utility maximization in a semimartingale model - Heli Huhtala (Bank of Finland, 2008)
It is well known that under certain assumptions the strategy of an investor maximizing his expected utility coincides with the mean-variance optimal strategy. In this paper we show that the two strategies are not equal in general and find the connection between a utility maximizing and a mean-variance optimal strategy in a continuous semimartingale model. That is done by showing that the utility maximizing strategy of a CARA investor can be expressed in terms of expectation and the expected quadratic variation of the underlying price process. It coincides with the mean-variance optimal strategy if the underlying price process is a local martingale.
URN:NBN:fi:bof-20140807117
Keywords: G11; C61; 330; mean-variance portfolios; utility maximization; dynamic portfolio selection; quadratic variation